Hak dan Kewajiban Warga Negara di Era Globalisasi Mahasiswa PGSD UNIPA Surabaya - Mar’atus Sholikhah; Dinda Ika Putri Yuni; Della Anggraeni; Vira Arfahunnisa; Rani Nurdiyanti; Grecencia Noyarto; Surti Padu Leba; Sabrina Ricke Fadilla; Agustina Viviliani Burhan; Dodo Nugroho; Merry Kristin Tekege; Suyono Suyono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to analyze the rights and obligations of citizens in the era of globalization with a focus on PGSD students at PGRI Adi Buana University (UNIPA) Surabaya. The era of globalization has brought significant changes in various aspects of life, including citizenship. Students as prospective educators have an important role in understanding and implementing their rights and obligations as good citizens. This research uses a qualitative descriptive method with data collection techniques through interviews, dokumentasi and literature study. The research results show that PGSD UNIPA Surabaya students have a good understanding of their rights and obligations, such as the right to education, freedom of opinion, and the obligation to pay taxes and respect the law. However, challenges in facing the era of globalization, such as the influence of foreign culture and technological advances, require adjustments and strengthening of citizenship education. This research concludes that increasing students' awareness and knowledge about the rights and obligations of citizens is very necessary to face the dynamics of globalization wisely.